PENYELENGGARAAN JENAZAH MUSLIM DI SITUASI NORMAL DAN PANDEMI COVID-19 - Gunaldi Ahmad (STIT Islamic Village Tangerang, 2021)
This study is titled The Implementation of Muslim Bodies in Normal Situations and the Covid 19 Pandemic. If Muslims witness other Muslims in a situation of near death or ihtidar should do the following: Recite the next sentence of the shahada confronting the person nearing death towards the Qibla. Then when he dies, close the eyes of the body. Then immediately bathed, prayed, and buried. This study found that specifically the Covid-19 pandemic since 2020 until now has brought a very large death toll around the world, so the handling of Covid-19 bodies also has a different procedure. This research generally explains that the management of bodies exposed to Covid-19, especially in bathing and converting, refining and burial processes is not much different from the process of organizing Muslim bodies in general. The reform must be carried out in accordance with medical protocol and carried out by the authorities, keeping in mind the provisions of sharia. As for mashing and burying is done as usual while keeping from being exposed to Covid 19. This research was conducted with qualitative research, inductive data collection. The primary sources are books, and journals.